Negative pole piece, secondary battery and device
By controlling the content of Li elements, full-filled expansion rate and compaction density of the negative electrode sheet in the silicon-based material, the problem of unstable interface of silicon oxygen materials during high-temperature storage is solved, and high energy density and excellent cycling performance are achieved. and calendar life battery.
Patent Information
- Application Number
- CN202411554196.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The interface instability of silicon oxygen materials during high-temperature storage, affecting the cracking and regeneration of the negative electrode solid electrolyte interface film, resulting in powdering of active particles and material falling off, shortening the calendar life of the battery.
By controlling the content of Li elements in the silicon-based material, the full-filled expansion rate of the silicon-based material and the compaction density of the negative electrode sheet, low lithium embedded expansion rate and high powder compaction density are achieved, and the battery cell volume is minimized. Reserved ratio to improve volume energy density, gram capacity and cycling performance.
It significantly improves the calendar life of the battery, improves energy density and cycling performance, alleviates the powdering problem of negative electrode active materials, and avoids the polarization effect.
Smart Images

Figure BDA0005116206940000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a negative electrode sheet, a secondary battery and a device. Background Art
[0002] With the widespread application of lithium-ion batteries in electric vehicles and energy storage, higher requirements are placed on the performance indicators of lithium-ion batteries, such as energy density and power density. In terms of negative electrode materials, the specific capacity of traditional graphite carbon-based negative electrode materials is limited, and it is difficult to meet the needs of high energy density batteries. Silicon-based materials, due to their high specific capacity, are negative electrode active materials for the next generation of electrochemical devices with application prospects. However, pure silicon materials have a volume expansion of 300% during the charging and discharging process, resulting in phenomena such as pole piece powdering, which affects the calendar life of the battery and restricts the application of silicon-based materials. Among them, silicon-oxygen materials are a branch of silicon-based materials. Because they have a mixed phase structure of silicon and oxide, they can effectively alleviate the volume effect of silicon during the charging and discharging process, and the volume expansion is greatly reduced compared to pure silicon, because it is easier to achieve commercial application.
[0003] However, current negative electrode sheets, secondary batteries and devices still need to be improved. Summary of the invention
[0004] The inventors found that the interface instability of silicon oxide materials during high-temperature storage not only affects the rupture and regeneration of the negative electrode solid electrolyte interface film (SEI film), but also causes the active particles to pulverize themselves and cause the active materials to fall off the current collector, shortening the calendar life of the battery.
[0005] In order to alleviate or solve at least one of the above problems to a certain extent, the present application provides a negative electrode plate, a secondary battery and a device, which can achieve a low lithium insertion expansion rate and a high powder compaction density by controlling the content of Li element in the silicon-based material, the full charge expansion rate of the silicon-based material, and the compaction density of the negative electrode plate, thereby minimizing the cell volume reserve ratio and improving the volume energy density, gram capacity and cycle performance.
[0006] On the one hand, the present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, wherein the negative electrode active material layer includes a carbon-based material and a silicon-based material, and the silicon-based material includes a pre-lithium silicon-oxygen material; the negative electrode plate satisfies: 6.6%≤1-D×(0.1×S+1.225) / 2.33+X≤20.4%; wherein, based on the total mass of the silicon-based material, the mass percentage content of the Li element is X; the full charge expansion rate of the silicon-based material is S; the compaction density of the negative electrode plate is D, in g / cm 3 .
[0007] Another aspect of the present application provides a secondary battery, which includes the negative electrode plate described above.
[0008] Another aspect of the present application provides a device, which includes the secondary battery described above.
[0009] The beneficial effects of this application are:
[0010] The negative electrode plate provided by the present application, the negative electrode active material layer of the negative electrode plate includes a carbon-based material and a silicon-based material, and the silicon-based material includes a pre-lithium silicon-oxygen material. By controlling the content of the Li element in the silicon-based material, the full charge expansion rate of the silicon-based material, and the compaction density of the negative electrode plate, on the one hand, it is possible to achieve a low lithium insertion expansion rate and a high powder compaction density, minimize the cell volume reservation ratio, improve the volume energy density, gram capacity and cycle performance, and significantly improve the calendar life; on the other hand, it is possible to effectively alleviate the internal pulverization of the negative electrode active material, avoid the polarization effect of the battery, and alleviate the expansion effect of the silicon-based material to avoid the porosity after expansion being too small, which is conducive to the full infiltration of the electrolyte, thereby improving the cycle performance. Therefore, based on the above improvements, the secondary battery of the present application has a higher energy density, excellent cycle performance and calendar life. DETAILED DESCRIPTION
[0011] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0012] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0013] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0014] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0015] 1. Negative electrode
[0016] The present application provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, wherein the negative electrode active material layer includes a carbon-based material and a silicon-based material, wherein the silicon-based material includes a pre-lithium silicon-oxygen material; the negative electrode plate satisfies: 6.6%≤1-D×(0.1×S+1.225) / 2.33+X≤20.4%; wherein, based on the total mass of the silicon-based material, the mass percentage content of the Li element is X; the full charge expansion rate of the silicon-based material is S; the compaction density of the negative electrode plate is D, in g / cm 3 .
[0017] The negative electrode plate provided in the present application, by controlling the content of Li element in the silicon-based material, the full charge expansion rate of the silicon-based material, and the compaction density of the negative electrode plate, can, on the one hand, achieve a low lithium insertion expansion rate and a high powder compaction density, minimize the cell volume reservation ratio, improve the volume energy density, gram capacity and cycle performance, and significantly improve the calendar life; on the other hand, it can effectively alleviate the internal pulverization of the negative electrode active material, avoid the polarization effect of the battery, and alleviate the expansion effect of the silicon-based material to avoid the porosity after expansion being too small, which is conducive to the full infiltration of the electrolyte, thereby improving the cycle performance. Therefore, based on the above improvements, the secondary battery of the present application has higher energy density, excellent cycle performance and calendar life.
[0018] In some embodiments, 6.6%≤1-D×(0.1×S+1.225) / 2.33+X≤20.4%. In some embodiments, 1-D×(0.1×S+1.225) / 2.33+X is 6.6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 20.4% or any value therebetween. In some embodiments, 11%≤1-D×(0.1×S+1.225) / 2.33+X≤16%. Thus, it is beneficial to exert high energy density and significantly improve calendar life. When the value of 1-D×(0.1×S+1.225) / 2.33+X is too large, it will cause serious pulverization of the active material particles, aggravating the polarization effect of the battery; when the value of 1-D×(0.1×S+1.225) / 2.33+X is too small, the porosity after expansion will be too small, which is not conducive to sufficient infiltration of the electrolyte, and further leads to cycle deterioration.
[0019] In some embodiments, based on the total mass of the silicon-based material, the mass percentage content of the Li element is X, 3%≤X≤13%. In some embodiments, X is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or any value therebetween. In some embodiments, 6%≤X≤9%. As a result, it is beneficial to achieve a balance between performance and cost. When the value of X is too large, the processability will deteriorate, such as gas production during slurrying, and the cost will increase significantly; when the value of X is too small, the first efficiency of the battery cell will be reduced, which is not conducive to the energy density.
[0020] In some embodiments, the full charge expansion rate of the silicon-based material is S, 100% ≤ S ≤ 180%. In some embodiments, S is 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180% or any value therebetween. In some embodiments, 130% ≤ S ≤ 160%. Thus, it is beneficial to give full play to the effect of silicon-oxygen materials in slowing down expansion. When the value of S is too large, the material will expand too much, causing stress concentration and eventually causing the silicon component to break; when the value of S is too small, it will lead to increased requirements for manufacturing and cost control.
[0021] In some embodiments, the compaction density of the negative electrode plate is D, in g / cm 3, 1.4≤D≤1.67. In some embodiments, D is 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.67 or any value therebetween. In some embodiments, 1.55≤D≤1.65. As a result, it is beneficial for the pole piece to exert the maximum energy density at a certain level of pressure resistance. When the value of D is too large, the material will be crushed during the rolling process, resulting in an increase in side reactions; when the value of D is too small, the reserved ratio of the battery cell volume will increase, affecting the energy density. The compaction density of the negative electrode pole piece can be adjusted according to the characteristics of the selected active material by conventional technical means in the field, such as controlling the pole piece coating thickness, coating temperature, etc.
[0022] In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage content of the silicon-based material is 1% to 20%. In some embodiments, the mass percentage of the silicon-based material is 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20% or any value therebetween. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage of the silicon-based material is 5% to 15%. As a result, it is beneficial to simultaneously meet the requirements of high energy density and long cycle performance of the battery cell. When the mass percentage value of the silicon-based material is too large, the pole piece will expand too much during the charge and discharge process of the battery cell, and the cycle performance will deteriorate; when the mass percentage value of the silicon-based material is too small, the energy density of the battery cell will be too low and will not meet the requirements.
[0023] In some embodiments, the general formula of the pre-lithium silicon oxide material is SiOx-Li, 0.5≤x≤1.6. In some embodiments, x is 0.5, 0.8, 1, 1.2, 1.4, 1.5, 1.6 or any value therebetween. In some embodiments, the pre-lithium silicon oxide material is a carbon-coated pre-lithium silicon oxide material. In some embodiments, the Dv50 of the pre-lithium silicon oxide material is 5μm to 11μm. In some embodiments, the Dv50 of the pre-lithium silicon oxide material is 5μm, 6m, 7m, 8m, 9m, 10, 11μm or any value therebetween. It should be noted that the above Dv50 can be obtained by laser particle size instrument testing.
[0024] In some embodiments, the carbon-based material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, carbon nanotubes and graphene. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage content of the carbon-based material is 80% to 98%. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage content of the carbon-based material is 80%, 85%, 90%, 95%, 98% or any value therebetween.
[0025] In some embodiments, the negative electrode active material layer further comprises a binder and a conductive agent. In some embodiments, the binder comprises: at least one of styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, epoxy resin and nylon. In some embodiments, the conductive agent comprises: at least one of carbon black, acetylene black, carbon nanotubes, carbon fibers, Ketjen black, artificial graphite, natural graphite and graphene.
[0026] In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage content of the binder is 0.6% to 3%, and the mass percentage content of the conductive agent is 0.8% to 1%. In some embodiments, based on the mass of the negative electrode active material layer, the mass percentage content of the binder is 0.6%, 1%, 1.5%, 2%, 2.5%, 3% or any value therebetween, and the mass percentage content of the conductive agent is 0.8%, 0.85%, 0.9%, 0.95%, 1% or any value therebetween.
[0027] In some embodiments, the carbon-based material is artificial graphite, and the silicon-based material is a pre-lithium silicon-oxygen material.
[0028] In some embodiments, the negative electrode current collector includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0029] In summary, the negative electrode plate provided by the present application can achieve a low lithium insertion expansion rate and a high powder compaction density, alleviate the expansion effect of silicon-based materials, minimize the cell volume reserve ratio, improve volume energy density, gram capacity and cycle performance, and significantly improve calendar life. Therefore, based on the above improvements, the secondary battery of the present application has higher energy density, excellent cycle performance and calendar life.
[0030] 2. Secondary battery
[0031] The present application also provides a secondary battery, the secondary battery comprising the above-mentioned negative electrode plate. Thus, the secondary battery can have all the features and advantages of the negative electrode plate described above, which will not be described in detail here.
[0032] In some embodiments, the secondary battery further includes a positive electrode sheet, an electrolyte, and a separator.
[0033] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0034] In some embodiments, the positive electrode active material comprises a lithium nickel transition metal oxide; wherein the lithium nickel transition metal oxide comprises LiNi m A 1-m O2, A includes at least one of cobalt, manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, yttrium, lanthanum, silver and niobium, 0.1≤m≤1.
[0035] In some embodiments, m is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any value therebetween.
[0036] In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, and Ni95.
[0037] In some embodiments, the positive electrode active material layer further includes a binder and a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc. In some embodiments, the conductive material includes: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0038] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be obtained by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0039] In some embodiments, the electrolyte includes a lithium salt, a solvent, and an additive.
[0040] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), trifluorosulfonyl lithium (LiTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium bis(fluoromalonate)borate (LiBFMB), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiDFP), lithium difluorobis(oxalatophosphate), and lithium 4,5-dicyano-2-(trifluoromethyl)imidazole (LiTDI).
[0041] In some embodiments, the mass percentage content of the lithium salt is 4% to 25% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage content of the lithium salt is 6% to 18%.
[0042] In some embodiments, the solvent includes at least one of a linear carbonate, a cyclic carbonate, and a carboxylic acid ester.
[0043] In some embodiments, linear carbonate is selected from at least one of dimethyl carbonate (DMC), diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate and fluorinated linear carbonate. In some embodiments, cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate and butylene carbonate. In some embodiments, carboxylic acid ester includes at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, gamma-butyrolactone and fluorinated carboxylic acid ester.
[0044] In some embodiments, the mass percentage content of the solvent is 40% to 80% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage content of the solvent is 50% to 70%.
[0045] In some embodiments, the additive includes at least one of a cyclic carbonate containing a carbon-carbon double bond, a phosphate containing a silane group, and a nitrile compound.
[0046] In some embodiments, the additive includes at least one of vinylene carbonate (VC), vinyl ethylene carbonate, tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), succinonitrile, adiponitrile, glutaronitrile and hexanetrinitrile. In some embodiments, the additive also includes at least one of methylene methyl disulfonate (MMDS), ethylene ethyl disulfonate, 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), vinyl sulfate (DTD), 4-methyl ethylene sulfate (PCS), 4-ethyl ethylene sulfate (PES), 4-propyl ethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES).
[0047] In some embodiments, the mass percentage content of the additive is 0.05% to 10% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage content of the additive is 0.1% to 5%.
[0048] In some embodiments, a separator is provided between the positive electrode plate and the negative electrode plate to prevent short circuit. The material and shape of the separator that can be used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0049] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene / polyethylene / polypropylene three-layer film can be selected.
[0050] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0051] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0052] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0053] In some embodiments, the method for preparing the secondary battery includes providing an electrode assembly, injecting liquid, packaging and forming. In some embodiments, the temperature of the forming is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C.
[0054] In some embodiments, the formation includes: charging to 3.9V at 0.05C current and standing for 24h at a temperature of 40°C to 50°C, such as 45°C, and a pressure of 150kgf to 750kgf, such as 600kgf, followed by charging to 4.4V at 0.1C, and then discharging to 2.8V at 0.2C.
[0055] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0056] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0057] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.
[0058] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0059] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0060] 3. Device
[0061] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module and battery pack. Therefore, the device can have all the features and advantages of the above-mentioned secondary battery, battery module or battery pack, which will not be repeated here.
[0062] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0063] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0064] Examples and Comparative Examples
[0065] Example 1
[0066] The steps of preparing the negative electrode plate are as follows: graphite, a negative electrode active material, and a silicon-based material SiOx-Li, 0.5≤x≤1.5 (specifically, pre-lithium silicon-oxygen material SiO 0.9 -Li), conductive agent carbon black (SP), dispersant CMC, binder SBR and PAA were mixed in a mass ratio of 82:14:1:0.6:1.2:1.2, deionized water was added, and the mixture was stirred under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on an 8μm negative electrode current collector copper foil, and the single-side coating weight was 8mg / cm 2 , and then through drying, rolling, hot pressing and other steps to obtain the negative electrode sheet. Among them, the mass percentage content of Li element in the silicon-based material is 3%, the full charge expansion rate of the silicon-based material is 177%, and the compaction density of the negative electrode sheet is 1.59g / cm 3 .
[0067] The preparation steps of the positive electrode plate are as follows: the positive electrode active material LiNi 0.8 Co0.1 Mn 0.1 O2, CNT (conductive agent carbon nanotube) / Super-P (conductive carbon black), binder polyvinylidene fluoride PVDF, the positive electrode active materials are in the weight ratio of: CNT / Super-P:PVDF=95:(1.0 / 2.0):2 in N-methylpyrrolidone NMP, and after sufficient homogenization, they are coated on a 12μm thick aluminum current collector, and then dried, rolled, hot pressed and other steps to obtain the positive electrode sheet.
[0068] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), fully dissolve the lithium salt LiPF6 in a mixed solution of EC / DEC / EMC (ethylene carbonate / diethyl carbonate / ethyl methyl carbonate) = 25 / 20 / 55 to prepare a 1 mol / L solution.
[0069] Diaphragm: PP / PE / PP (polypropylene / polyethylene / polypropylene) three-layer composite diaphragm is used.
[0070] Preparation of lithium-ion secondary battery: The prepared positive electrode sheet, separator (PP / PE / PP three-layer composite film), and negative electrode sheet are overlapped in turn, with the separator being located between the positive electrode sheet and the negative electrode sheet to obtain a bare cell, and the bare cell is placed in a punched aluminum-plastic film soft package shell, and after being fully dried, the prepared electrolyte is injected, and the battery is placed at 45°C for 48h, and formed in a high-temperature fixture (the formation conditions are: temperature 45°C, pressure 600kgf, 0.05C current charging to 3.9V and standing for 24h, then 0.1C charging to 4.25V, and then 0.2C discharge to 2.5V, after secondary sealing, conventional capacity division is performed.
[0071] Examples 2 to 12 and Comparative Examples 1 to 5
[0072] Examples 2 to 12 and Comparative Examples 1 to 5 are achieved on the basis of Example 1 by adjusting the mass percentage content of the Li element in the silicon-based material, the full charge expansion rate of the silicon-based material, the compaction density of the negative electrode plate, etc. The specific adjustment measures and detailed data are shown in Table 1.
[0073] Test Method
[0074] 1. Test of the mass percentage content of Li element in silicon-based materials
[0075] The emission spectrum or atomic absorption spectrum of lithium in the sample (pre-lithium silicon-oxygen material) is measured by plasma emission spectrometry (ICP) to obtain the lithium concentration. The instrument automatically calculates the mass percentage content of the Li element based on the total mass of the silicon-based material.
[0076] 2. Full charge expansion rate test of silicon-based materials
[0077] Preparation of silicon-based negative electrode sheet: Silicon-based material (negative active material), conductive agent carbon black and PAA are homogenized in a mass ratio of 80:10:10 to obtain a uniformly dispersed slurry, which is then coated on a 6μm or 8μm copper foil, dried at 100°C, and then rolled to obtain a pure silicon negative electrode sheet for later use. The single-sided surface density of the obtained pure silicon-based negative electrode sheet is 4mg / cm 2 , compacted density is 1.3g / cm 3 .
[0078] The thickness of the pure silicon-based material negative electrode plate after cold pressing and rebounding is recorded as Ts0, and the cold pressed negative electrode plate is made into a button battery with a lithium plate, a separator, and an electrolyte. At 25°C, the button battery is charged and discharged with a voltage range of 0.005-2V. First, it is discharged to 0.005V at a constant current of 0.1C, and then it is discharged to 0.005V at a constant current of 0.01C. After standing for 10 minutes, it is then discharged to 0.005V at a constant current of 0.01C. After standing for 30 minutes, it is charged to 2.0V at a constant current of 0.1C; the charge and discharge cycle is repeated for 3 weeks. Then the button battery is discharged to 0.005V at a current of 0.1C, the button battery is disassembled and the thickness of the negative electrode plate is tested, which is recorded as Ts1. The full charge expansion rate of the negative electrode plate is: (Ts1-Ts0) / Ts0×100%.
[0079] 3. Negative electrode compaction density test
[0080] The compaction density of the negative electrode sheet = the single-sided surface density of the negative electrode sheet (g / cm 2 ) / Thickness of one side (cm). Among them, when the negative electrode active material layer is coated on one side of the negative electrode sheet, a piece of negative electrode sheet is cut, its mass is weighed and recorded as M1, and then the negative electrode active material layer on the negative electrode sheet is scraped off, and its mass is weighed and recorded as M2, and the area of the negative electrode sheet is measured and recorded as V. The single-sided surface density of the negative electrode sheet = (M1-M2) / V, and the thickness of the single side of the negative electrode active material layer is the total thickness of the negative electrode sheet minus the thickness of the negative electrode collector (such as foil); when the negative electrode active material layer is coated on both sides of the negative electrode sheet, a piece of negative electrode sheet is cut, its mass is weighed and recorded as M1, and then the negative electrode active material layer on both sides of the negative electrode sheet is scraped off, and its mass is weighed and recorded as M2, and the area of the negative electrode sheet is measured and recorded as V, and the single-sided surface density of the negative electrode sheet = (M1-M2) / 2V, and the thickness of the single side of the negative electrode active material layer is the total thickness of the negative electrode sheet minus the thickness of the negative electrode collector (such as foil) and then divided by 2. Among them, the mass can be weighed by a standard balance and the thickness can be measured by a micrometer.
[0081] 4. 25℃ Cyclic Capacity Retention Test
[0082] At 25°C, the prepared lithium-ion secondary battery was charged to 4.4V at a constant current rate of 1C, and then charged at a constant voltage until the current was less than 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a rate of 1C, and the initial discharge capacity was recorded. The lithium-ion secondary battery was charged and discharged 300 times (300cls) by the above method, and the discharge capacity of each time was recorded. The capacity retention rate of the lithium-ion secondary battery after 300 cycles at 25°C = the discharge capacity of the 300th time / initial discharge capacity × 100%.
[0083] 5. 1C / 1C cycle performance test
[0084] At 25°C, first charge at 1C constant current to 4.25V, then charge at constant voltage to a current of 0.05C. After standing for 10 minutes, discharge at 1C constant current to 2.5V. Perform a cycle test in this full charge and discharge form until the discharge capacity of the lithium-ion battery decays to 80% of the initial capacity, and record the number of cycles at this time.
[0085] Test Results
[0086] Table 1
[0087]
[0088] It can be seen from Examples 1 to 12 and Comparative Examples 1 to 5 that the present application controls the content X of the Li element in the silicon-based material, the full charge expansion rate S of the silicon-based material, and the compaction density D of the negative electrode plate. On the one hand, it is possible to achieve a low lithium insertion expansion rate and a high powder compaction density, thereby minimizing the cell volume reservation ratio, improving the volume energy density, gram capacity and cycle performance, and significantly improving the calendar life; on the other hand, it is possible to effectively alleviate the internal pulverization of the negative electrode active material and avoid the polarization effect of the battery. By alleviating the expansion effect of the silicon-based material and avoiding the porosity after expansion being too small, it is beneficial to fully infiltrate the electrolyte, thereby improving the cycle performance.
[0089] By comparing Comparative Example 1 with Examples 1 to 12, it can be seen that in Comparative Example 1, due to the excessively large value of D, the value of 1-D×(0.1×S+1.225) / 2.33+X is too small, which will cause the negative electrode material to be crushed during the rolling process, increase the side reactions, and cause the porosity after expansion to be too small, which is not conducive to sufficient infiltration of the electrolyte, and further leads to cycle deterioration, and the capacity retention rate and cycle performance of the secondary battery are also poor.
[0090] By comparing Comparative Examples 2 to 4 and Examples 1 to 12, it can be seen that in Comparative Examples 2 to 4, due to the small value of X and the large value of S, the value of D×(0.1×S+1.225) / 2.33+X is too small, which will lead to a decrease in the first efficiency of the battery cell, which is not conducive to the energy density. The silicon-based material expands too much, causing stress concentration and eventually causing the silicon component to break, further resulting in the porosity after expansion being too small, which is not conducive to sufficient infiltration of the electrolyte, and then leading to cycle deterioration, and the capacity retention rate and cycle performance of the secondary battery are also poor.
[0091] By comparing Comparative Example 5 with Examples 1 to 12, it can be seen that in Comparative Example 5, due to the excessively large value of X, the value of D×(0.1×S+1.225) / 2.33+X is too large, which leads to poor processability, such as gas production during slurrying, and a significant increase in cost. At the same time, the active material particles are severely pulverized, which aggravates the polarization effect of the battery, and the capacity retention rate and cycle performance of the secondary battery are also poor.
[0092] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A negative electrode plate, characterized in that: It includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a carbon-based material and a silicon-based material, and the silicon-based material includes a pre-lithium silicon-oxygen material; The negative electrode sheet satisfies: 6.6%≤1-D×(0.1×S+1.225) / 2.33+X≤20.4%; Wherein, based on the total mass of the silicon-based material, the mass percentage content of the Li element is X; The full-fill expansion rate of the silicon-based material is S; The compaction density of the negative electrode sheet is D, in g / cm 3 .
2. The negative electrode sheet according to claim 1, characterized in that: 11%≤1-D×(0.1×S+1.225) / 2.33+X≤16%.
3. The negative electrode sheet according to claim 1, characterized in that: 3% ≤ X ≤ 13%; and / or 100% ≤ S ≤ 180%; and / or 1.4≤D≤1.67。 4. The negative electrode sheet according to claim 3, characterized in that: 6% ≤ X ≤ 9%; and / or 130% ≤ S ≤ 160%; and / or 1.55≤D≤1.65。 5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The general formula of the pre-lithium silicon-oxygen material is SiOx-Li, 0.5≤x≤1.
6.
6. The negative electrode sheet according to claim 5, characterized in that: The pre-lithium silicon-oxygen material is a carbon-coated pre-lithium silicon-oxygen material; and / or The Dv50 of the pre-lithium silicon oxide material is 5 μm to 11 μm.
7. The negative electrode sheet according to claim 1, characterized in that: Based on the mass of the negative electrode active material layer, the mass percentage content of the silicon-based material is 1% to 20%; and / or The carbon-based material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, carbon nanotubes and graphene; based on the mass of the negative electrode active material layer, the mass percentage content of the carbon-based material is 80% to 98%; and / or The negative electrode active material layer also includes a binder and a conductive agent; wherein the binder includes: at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylic acid, polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, epoxy resin and nylon; the conductive agent includes: at least one of carbon black, acetylene black, carbon nanotubes, carbon fiber, Ketjen black, artificial graphite, natural graphite and graphene; based on the mass of the negative electrode active material layer, the mass percentage content of the binder is 0.6% to 3%, and the mass percentage content of the conductive agent is 0.8% to 1%.
8. The negative electrode sheet according to claim 1, characterized in that: The carbon-based material is artificial graphite, and the silicon-based material is pre-lithium silicon-oxygen material.
9. A secondary battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 1 to 8.
10. A device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.